Analisis Pelaksanaan Penilaian Kinerja Karyawan CV. Awing Citra Abadi Teknik - Zhafira Aulinasari; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Employee performance is the result of quality and quantity standards set by the organization. Employee performance will influence the success of an organization, so employee performance has a close relationship with performance appraisal. Performance appraisal or what can also be called performance evaluation, is an organization's effort to assess the achievements of its employees for the purpose of increasing their productivity. However, sometimes companies still make poor assessments so that their goals are not achieved. This results in a decline in company targets. Performance appraisal does not only look at the results of the work that employees do, but can also be seen from how the employee completes his work. This research uses a qualitative descriptive approach through case studies, namely by analyzing existing problems. This qualitative research uses primary data and secondary data. The primary data for this research was obtained through observation, interviews and documentation, while the secondary data was obtained through previous research. The population in this study were employees of CV Awing Citra Abadi Teknik with a total of 20 employees. The purpose of this research is to determine the implementation of employee performance appraisals at CV Awing Citra Abadi Teknik which includes procedures for implementing employee performance appraisals, efforts to encourage the implementation of employee performance appraisals, and employee performance appraisal procedures.